Physical attributes of Cambisol in apple (Malus domestica Borkh. cv. Gala) orchard under different weed management systems in Urubici, Plan alto Serrano SC, Brasil (2017)
The aim of this research was to evaluate the physical attributes of Cambisol in apple (Malus domestica Borkh. cv. Gala) orchard under different weed management systems in the state of Santa Catarina (SC), Brazil. The treatments were as follows: control (no weed management), chemical desiccation and mowing. We took samples of undisturbed soil at depths of 0-5, 5-10, 10-15 and 15-20 cm. We evaluated hydraulic conductivity (HC); bulk density (BD); soil penetration resistance (Pr); total porosity (TP), macropores (MaP), micropores (MiP); soil aggregation indices such as arithmetic and geometric mean diameter of air-dried and water-stable aggregates (AMDad, AMDws, GMDad, GMDws, respectively); aggregate stability index (ASIAMD and ASIGMD) and volumetric water content (VWC). We also carried out principal component analysis (PCA) with the data. The mowing or desiccation treatments increased BD at the 15-20 cm depth compared to control. The mowing treatment had the highest ASIGMD while desiccation contributed to the lowest ASIGMD. The desiccation treatment decreased AMDws (0-10 cm), ASIAMD (0-5 cm) GMDws (5-10 cm) and reduced HC by 26% and 22%, respectively, compared to the mowing and control treatments. Through PCA we were able to separate the three treatments. The mowing treatment was correlated with HC, VWC at pressure of 600 kPa and ASIGMD; desiccation was correlated with BD and Pr; and control with ASIAMD, MaP and TP.